Investigation of performance parameters of building thermal battery - Zhang Y.Z.; Wang S.G.; Jiang S.; Wang J.H.; Wu X.Z.; Zhang T.F. (E3S Web of Conferences, 2022)
The concept of a building thermal battery refers to storing the supplied heat and releasing it the another time through radiation and convection. The introduction of building thermal battery performance has created a more convenient solution to the problems of building load estimation, control and optimization, building-grid integration, etc. Some literatures have expanded the original definition of building thermal batteries, including PV RE (photovoltaic renewable energy), HVAC and other units. Starting from the building body, this investigation studies a building energy system. With reference to the performance parameters of traditional rechargeable batteries, the corresponding performance parameters of building thermal batteries are developed. The RC model is further used to model the performance parameters of the building thermal battery respectively. Among them, the corresponding parameter values of the RC model are obtained by parameter identification. Finally, the heat storage and heat release characteristics of the building integrated energy system are obtained. It makes the application of buildings as batteries more flexible in the urban energy network.